Relationship between autonomic markers of heart rate and subjective indicators of recovery status in male, elite badminton players - Bisschoff, C. A.; Coetzee, B.; Esco, M. R. (Journal of Sports Science & Medicine, 2016)
The primary aim of the study was to determine if heart rate variability (HRV), and heart rate recovery (HRR) are related to several subjective indicators of recovery status (muscle soreness, hydration status, sleep quality and quantity as well as pre-competition mood states) for different match periods in male, elite, African, singles badminton players. HRV and HRR were measured in twenty-two badminton players before (pre-match), during (in-match), after (post-match) and during rest periods (in-match rest) of 46 national and international matches. Muscle soreness, hydration status, and sleep quality and quantity were measured on a daily basis whereas mood states were measured just before each match via questionnaires. Prior to each match warm-up, players were fitted with a Fix Polar Heart Rate Transmitter Belt to record heart rate every second during each match and HRR during service breaks and after matches. Kubios HRV software was used for final HRV analyses from the series of R-R-intervals. A strong, significant canonical correlation (Rc = 0.96, p = 0.014) was found between HRV, HRR and subjective indicators of recovery status for the in-match period, but only strong, non-significant relationships were observed for pre-match (Rc = 0.98, p = 0.626) and post-match periods (Rc = 0.98, p = 0.085) and a low non-significant relationship (Rc = 0.69, p = 0.258) for the in-match rest period. Canonical functions accounted for between 47.89% and 96.43% of the total variation between the two canonical variants. Results further revealed that Ln-HFnu, the energy index and vigour were the most prominent variables in the relationship between the autonomic markers of heart rate and recovery-related variables. In conclusion, this study proved that subjective indicators of recovery status influence HRV and HRR measures obtained in a competitive badminton environment and should therefore be incorporated in protocols that evaluate these ANS-related parameters.